Can You please show the solution of the following sums :-
  1. (a2-1)(b2-1)+4ab
  2. x4+x2+1

Asked by jyotiharish2001 | 13th Jun, 2015, 06:51: PM

Expert Answer:

Assuming that the question asks to factorise the given expressions, the explanation is as follows:
1. (a2-1)(b2-1)+4ab = a2b2-a2-b2+1+4ab= a2b2-a2-b2+1+2ab+2ab
Rearranging the terms, we get 
=(ab+1)2 - (a-b)2
2. x4+x2+1 =  x4+2x2-x2+1
Rearranging the terms, we get
(x4+2x2+1) - x2
=(x2+1)2 - x2

Answered by satyajit samal | 14th Jun, 2015, 09:11: AM